AIRE: From promiscuous molecular partnerships to promiscuous gene expression. Issue 1 (2nd November 2015) - Abramson, Jakub; Goldfarb, Yael
Abstract : Autoimmune regulator (AIRE) is a unique transcriptional regulator that induces promiscuous expression of thousands of tissue‐restricted antigens (TRAs) in medullary thymic epithelial cells (mTECs), a step critical for the induction of immunological self‐tolerance. The past 15 years have seen dramatic progress in our understanding of how AIRE induces immunological self‐tolerance on a molecular level. This major advancement can be greatly attributed to the identification of a large variety of proteins that physically associate with AIRE, supporting and regulating its transcription‐transactivation capacity. These diverse molecular partnerships have been shown to play roles in shuttling AIRE to the nucleus, securing AIRE's interaction with nuclear matrix and chromatin, releasing RNA polymerase‐II from its stalled state and potentiating AIRE‐mediated gene expression, among others. In this review we discuss the relationship of AIRE with its vast and rather diverse repertoire of partners and highlight how such "promiscuous partnerships" contribute to the phenomenon of "promiscuous gene expression" in the thymus.